Pengaruh Pemberian Pendidikan Gizi tentang Gizi Seimbang terhadap Pengetahuan Masyarakat Kampung Kalisusu Kabupaten Nabire - Nur Susan Iriyanti Ibrahim; Nur Al-faida; Elis Bre Boli (Universitas Batanghari Jambi, 2022)
At the present time, nutritional problems in Indonesia have been changed to triple burden of malnutrition. The problem of macronutrient deficiencies such as malnutrition and stunting, macronutrient excess such as obesity, and micronutrient deficiencies such as anemia. Obesity is a major factor in the occurrence of non-communicable diseases (NCD). Data in Indonesia based on Riskesdas in 2018 shows that the incidence of PTM that occurs in Indonesian society includes stroke, diabetes mellitus, and hypertension which has increased every year. The prevalence of stroke in the population aged more than 15 years was 7% in 2013 and 10.9% in 2018. The prevalence of diabetes mellitus in the population aged more than 15 years was around 1.2% in 2013 and in 2018 it was 2%. The incidence of obesity with a BMI above 27 kg/m2 in 2007 was 10.5%, in 2013 was 14.8%, and in 2018 was 21.8%. Obesity is a major factor in the occurrence of non-communicable diseases (PTM). Nutrition education is one of the efforts that can be done to improve consumption patterns or healthy behavior of the community. The purpose of this study is to provide nutrition education related to balanced nutrition guideline and evaluate the interventions that have been given. This research is a type of quantitative research with a cross sectional design. With the target of 30 respondents from the Kalisusu Nabire Village. The results of this study indicate that after nutrition education is carried out, respondents' knowledge about balanced nutrition was increases. The conclusion of this study was nutrition education with counseling methods can increasing the nutritional knowledge.